Factors associated with the prevalence of diseases in the scalp: a prospective study in Mugdha Medical College and Hospital, Dhaka, Bangladesh - Shahidul Hoq, Abu Jafar M.; Salah Uddin, Muhammad; Sultana, Fahmida (International Journal of Research in Medical Sciences, 2024)
Background: The scalp skin is distinct from other areas of the body due to its unique characteristics, including the density of hair follicles and the high rate of sebum production. So of creating a dark, warm, and moist environment and various types of diseases in the scalp are usually occur. Methods: This was a prospective cross-sectional study conducted at the Department of Dermatology in Mugdha Medical College and Hospital during January, 2023 to June, 2023. A total of 60 clinically diagnosed scalp diseases patients were enrolled in this study. The collected data were analysed using Statistical Package for Social Sciences (SPSS) software, version-23.0. The ethical clearance of this study was obtained from the Institutional Review Board (IRB) of Mugdha Medical College and Hospital, Dhaka, Bangladesh. Results: A total of 60 clinically diagnosed scalp diseased OPD patients aged 1 to 60 years were enrolled in this study. Among the patients, 30 (50%) were male and 30 (50%) were female. According to multinomial logistic regression, the major factors contributed to exposing the diseases on scalp were age, sex, educational level, occupation, socio-economic condition, family history and behaviour (OR>1 or OR<1). Conclusions: This study prevailed, Age, sex, behaviour, family history, occupation, education level, socio-economic condition, hygiene, associated systemic diseases, hair grooming are the factors associated with the prevalence of diseases on the scalp of humans.